If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + -3) = 2(12x + 8) Reorder the terms: 6(-3 + 4x) = 2(12x + 8) (-3 * 6 + 4x * 6) = 2(12x + 8) (-18 + 24x) = 2(12x + 8) Reorder the terms: -18 + 24x = 2(8 + 12x) -18 + 24x = (8 * 2 + 12x * 2) -18 + 24x = (16 + 24x) Add '-24x' to each side of the equation. -18 + 24x + -24x = 16 + 24x + -24x Combine like terms: 24x + -24x = 0 -18 + 0 = 16 + 24x + -24x -18 = 16 + 24x + -24x Combine like terms: 24x + -24x = 0 -18 = 16 + 0 -18 = 16 Solving -18 = 16 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1s^2=1s^2 | | -9+15b=-87 | | 14x^2+3=23x | | 5-3/8s=5/6 | | 36w^2-121g^2=0 | | s^2= | | A/3-2=15 | | 8+12m-2=6m+30-2m | | 14x^3=23x | | 0=-11+-10(0) | | x^2(x^2-9)-25(x^2-9)=0 | | 3w-19w=144 | | 3x+3x=12 | | (-15/7)p=-3 | | 5ln(7x)=10 | | 6y+12=3x | | 26y-31=y-(-33) | | -3=-10z+6 | | 2r+15r=119 | | 9x^4-19x^2+2=0 | | z/4=-22 | | x=-11+10(1) | | -3x^2+x+70=0 | | 8/-10=y | | 36v^2+60vg+25g^2=0 | | 8+1/6y=0 | | 7/8-1/5 | | 30x^3+39x^2-9x=0 | | 4-(3x-5)=-4(3x-2) | | 2u^2-8= | | B(x-a)=c | | 3(-2)=6 |